Підбійні поховання кочівників ХІІ-ХІІІ ст. на Сіверському Дінці - Харламова, А.О. (Археологія, 2015)
У статті розглядаються підбійні поховання кочівників розвинутого середньовіччя в середній течії Сіверського Дінця. Автор робить висновок, що вони входять до одного типологічного ряду та можуть належати донецькому об’єднанню половців. В статье рассмотрены подбойные погребения кочевников ХІІ—ХІІІ вв., которые группируются в бассейне сред него течения Северского Донца. Объединяет их конструкция могилы — с подбоем, помещение покойника в вы долбленную колоду, наличие оружия в погребении, помещение в могилу, как правило, целого занузданного коня на животе с поджатыми ногами, отсутствие следов жертвенной пищи. Таким образом, данные погребения отно сятся к одному типу и находят аналогии как в Поросье, куда переселилась часть кочевников, перейдя на службу к русским князьям, так и на Алтае в среде древних тюрок.
Автор сознательно не учитывал так называемые «одиночные» погребения кочевников развитого средневе ковья, поскольку они не дают практически никакой информации ни о времени погребения, ни об этнической принадлежности покойника. Что касается подбойных погребений, то они могут указывать на довольно высокий социальный статус покойника, о чем говорит сравнительно богатый погребальный инвентарь, но в то же время они выступают и этническим маркером, поскольку способы помещения коня в могилу, да и сами погребальные конструкции кочевников развитого средневековья значительно отличались. Подбойные погребения в среднем течении Северского Донца датируются половецким временем, их можно связать с так называемым донецким объединением половцев, которое кочевало здесь в этот период. In the article, discussed are undercut burials of the 12th and the 13th centuries nomads grouped in the basin of the Siverskyi Donets River middle stream area. They are united by the grave structure: with an undercut, the buried is placed in a hollowed out log, presence of weapon in the burial, horse in bridle, usually the whole, placed on its stomach with its legs crossed under, and lack of funeral feast traces. Thus, the data from the burials refer to a single type and find their analogies both in the Ros River region where part of the nomads moved to, turning to service of Rus princes, and in altai in the ancient Turks’ milieu.
The author deliberately did not take into consideration so called «single» burials of the nomads of the high Mediaeval period because they don’t present any information neither on the date of the burial, nor on the ethnic identity of the buried. Concerning the undercut burials, they can indicate quite a high social status of the dead which is evidenced by relatively rich burial inventory, but at the same time, they can be also ethnic markers because the ways of placing the horse in the grave, as well as the burial structures themselves significantly varied in the high Mediaeval period. Undercut burials in the middle stream of the Siverskyi Donets River are dated by the Cumans period and they can be related with so called Donets Cumans’ union which roamed here in this period.